Case Report: A Rare Abdominopelvic Arteriovenous Malformation: Originating From Splenic Artery and Draining Into Portal Vein - Li, Xin; Li, Jiehua; Wang, Mo; Wang, Junwei; Wang, Lunchang; He, Hao; Li, Ming; Li, Quanming; Shu, Chang (Frontiers in Cardiovascular Medicine, 2022)
Background Abdominopelvic arteriovenous malformation is an uncommon congenital vascular lesion, for which the diagnosis and treatment are usually difficult. Though embolization and sclerotherapy are the primary treatment strategies, traditional surgical resection remains a valuable option. Case Presentation Herein, we present a 32-year-old female diagnosed with a massive abdominopelvic arteriovenous malformation that originates from the splenic artery and drains into the portal vein. The vascular lesion was evaluated with multiple imaging modalities and then surgically resected successfully. The patient was discharged post-operatively on day 6 and free of symptoms during the 12-month follow-up. Conclusion To our knowledge, the presented abdominopelvic arteriovenous malformation is the first to be reported in the literature, with such a rare condition originating from the splenic artery and draining into the portal vein.